Impulse eaudiobook - Hopkins, Ellen (HighBridge Audio, 2009)
Three teens who have attempted suicide meet in a psychiatric hospital, battle their demons, and begin to heal.The handsome son of wealthy parents, Connor has everything anyone could want-except his family's love and affection. Jailed for years after killing his mother's child-molesting boyfriend, Tony is confused about his sexuality. Manic-depressive Vanessa cuts herself. All three stories intertwine in a brutally honest story about pain and resilience.